2021
DOI: 10.1071/an20459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial diversity in rumen and small intestine of Xinong Saanen dairy goats using 16S rRNA gene high-throughput sequencing

Abstract: Context. Gastrointestinal microorganisms play an important role in ruminant digestion and metabolism, immune regulation and disease prevention and control. Different parts of the digestive tract have different functions and microbial community structures.Aims. This study aims to explore the microbial diversity in the rumen and the small intestine of Xinong Saanen dairy goats.Methods. Rumen fluid and jejunum fluid from three Xinong Saanen dairy bucks with the average slaughter weight of 33.93 AE 0.68 kg were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The most abundant genera in the stomachs were Prevotella , Rikenellaceae_RC9_gut_group and Christensenellaceae_R-7_group , which reached up to 44.5% in some of these GIT compartments. In previous studies on goats [ 32 , 44 ], members of Prevotella and families Rikenellaceae and Christensenellaceae were also found predominant in the rumen. In the present study, Prevotella alone reached up to 30.3% of the total abundance.…”
Section: Discussionmentioning
confidence: 91%
“…The most abundant genera in the stomachs were Prevotella , Rikenellaceae_RC9_gut_group and Christensenellaceae_R-7_group , which reached up to 44.5% in some of these GIT compartments. In previous studies on goats [ 32 , 44 ], members of Prevotella and families Rikenellaceae and Christensenellaceae were also found predominant in the rumen. In the present study, Prevotella alone reached up to 30.3% of the total abundance.…”
Section: Discussionmentioning
confidence: 91%
“…First, a total of 1,023,714 clean reads with an average length of 1452 bp were sequenced from the microbial V1–V9 region, and 6669 distinct OTUs were ultimately identified, which were higher than previously sequenced on sheep (322–789 OTUs) (Wang et al 2017 ) and goats (1118 OTUs) (Li et al 2022 ), indicating that we were able to investigate the bacterial community with a higher resolution.…”
Section: Discussionmentioning
confidence: 96%
“…The Xinong Saanen dairy goat is a cultivated breed based on the Swiss Saanen dairy goat, which is known for high milk yield, outstanding reproductive performance, and stable genetic performance. Currently, more than half of China’s dairy goats have the lineage of Xinong Saanen dairy goats (Li et al 2022 ). However, research into their microbiome has tended to focus on the rumen or feces, without systematic research into the entire GITs.…”
Section: Introductionmentioning
confidence: 99%
“…All findings indicated that bacteria played an important role in nutrient digestion and absorption of ruminants. The fiber was digested through the bacteria in the rumen into volatile fatty acids, such as acetic acid, propionic acid, and butyric acid 57 , 58 . Meanwhile, the bacteria could convert the nitrogen-containing substances into amino acids and provided the nitrogen source for ruminants.…”
Section: Discussionmentioning
confidence: 99%